Biotherapies targeting T and B cells: from immune suppression to immune tolerance. (August 2015) - Chatenoud, Lucienne
Highlights: T and B lymphocyte receptors are major therapeutic targets. CD3 monoclonal antibodies afford operational tolerance. For each biotherapy the risk/benefit ratio should be carefully considered. Abstract : The field of immunotherapy has undergone a major rejuvenation with the development of monoclonal antibodies and fusion proteins targeting specialized receptors of T and B lymphocytes or cytokines relevant for the differentiation of these cells. This review will focus on autoimmunity, probably the field that benefited most from these new biological therapies that very significantly impacted the modalities of patient's care. The aim is to present the agents which constitute major disease modifying drugs for the treatment of chronic invalidating autoimmune diseases. In doing so, we shall distinguish between agents that globally depress immune responses and those that may selectively target the harmful autoimmune response over long-term while preserving the capacity of the host to react normally to exogenous antigens, in other words, agents promoting 'operational tolerance'.